Experimental simulation of arsenic desorption from Quaternary aquifer sediments following sea water intrusion. (December 2017) - Morelli, Guia; Rimondi, Valentina; Benvenuti, Marco; Medas, Daniela; Costagliola, Pilario; Gasparon, Massimo
Abstract: Alluvial sediments from the coastal area in southern Tuscany (Italy) characterized by a significant As anomaly (As >500 mg/kg) are subjected to seawater intrusion due to groundwater exploitation. Sequential extractions and kinetic experiments were carried out on Quaternary alluvial sediments to quantify the interaction between As oxianions (adsorbed on mineral surfaces) and Cl − in solutions and to establish if this mechanism may contribute to the release of As in groundwater. The natural water-rock interaction in the aquifer was simulated in two experiments by saturating the samples with four solutions with increasing chlorinity for different time. Firstly, a rapid change in the aquifer salinity (e.g. fast seawater intrusion, groundwater over pumping) was simulated by an interaction sediment/solution of 24 h. Solutions with Cl − ≤2000 mg/L extracted up to 76 μg/kg of As, while seawater (Sol 4(24) : Cl − ∼18, 500 mg/L) extracted up to 161 μg/kg of As. In a second experiment, the ingression of water with increasing salinity in the acquifer, followed by the withdrawal of the water after progressively longer interaction times with the aquifer sediments, was simulated. The timing of the As-Cl reaction was constrained by saturating the samples with four solutions with increasing salinity (Sol1(84) : Cl − ∼0 mg/L; Sol2(84) Cl − = 250 mg/L; Sol3(84) Cl − = 2000 mg/L; Sol4(84) : Cl − = 15, 886 mg/L) that interacted with the sediment samples for longer saturation times (up to 21 days for each solution). After saturation with the previous three solutions up to 62 μg/kg of As were extracted by seawater, following a salinity increase from 2000 mg/L Cl to a chlorinity close to seawater, representing ∼60% of the exchangable As fraction in the sediments. Our results constrained the timing of sediment/solution interaction of As desorption and showed that after a rapid intrusion of seawater or after a relatively long period of interaction with saline solutions an aquifer with similar geology releases in groundwater concentrations of As exeeding the 10 μg/L limit for drinking water. Also, this study estimated the potential effects caused by the ingression of seawater in lowland alluvial coastal areas induced by groundwaters exploitation or by extreme weather events. Such information is crucial for management authorities to mitigate and predict the effects of As hazard in groundwater driven by changes in the environmental aquifer conditions (e.g. seasonal fluctuations of the water table and/or changes in salinity of coastal aquifers), which are becoming increasingly frequent as consequence of climate change. Highlights: Natural water-rock interaction in an aquifer was simulated by desorption experiments. Timing of interaction and variations in water salinity control arsenic desorption. Rapid intrusion of seawater in high As aquifer sediments may release >10 μg/L As.